Implementasi Kebijakan Peraturan Daerah No. 05 Tahun 2016 tentang Pelayanan Terpadu Satu Pintu - Yudianingsih, Nita; Hambali, Hambali (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to examine the implementation of the One-Stop Integrated Service (PTSP) policy based on Regional Regulation No. 05 of 2016 in Pejangkungan Village, and to identify supporting and inhibiting factors in its implementation. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation, as well as data analysis of the interactive model of Miles, Huberman, and Saldana. The results of the study indicate that the implementation of PTSP has brought positive changes to the pattern of public services, marked by a good understanding of regulations, the preparation of SOPs, and commitment from village officials. However, its implementation still faces obstacles, such as limited human resources, minimal technical training, inadequate infrastructure, and weak evaluation and monitoring systems. The conclusion shows that although the implementation of the policy is quite effective in changing the service system to be more structured and efficient, strategies are needed to strengthen the capacity of the apparatus, utilize technology, and provide ongoing support from the local government so that the policy implementation runs optimally.   Keywords: Policy Implementation, Public Services, Village, One-Stop Integrated Service, Resources